Enacting ‘true business sustainability’ − Market shaping for environmental impact - Syväri Mariia; Tähtinen Jaana; Nordberg-Davies Sini (Elsevier, 2025)
Market-shaping research on firms’ efforts to transform markets for environmental aims is scarce and limited to incumbent actors’ efforts to replace existing technologies with more sustainable alternatives. While important, these studies implicitly adhere to the ‘business case for sustainability’ approach, in which CSR is harnessed to facilitate profitability and competitive advantage. We offer a new perspective by examining market shaping explicitly aimed at inducing environmental impact. Using the lens of for-profit hybrid firms, which enact a ‘true business sustainability’ approach by blending environmental impact goals with commercial objectives, we explore the case of a hybrid shaping an existing EU regulation-born ‘sustainability market’ built around the Guarantees of Origin for renewable electricity. We contribute to the contextual understanding of market shaping for sustainability by presenting a model of firm-level market shaping for environmental impact, unfolding through six intertwined processes inherently connected to the organization’s development.